Integrity and life estimation of turbine runner cover in a hydro power plant (Fracture and Structural Integrity, 2016)
This paper presents integrity and life estimation of turbine runner cover in a vertical pipe turbines,Kaplan 200 MW nominal output power, produced in Russia, and built in six hydro-generation units ofhydroelectric power plant „Đerdap 1” in Serbia. Fatigue and corrosion-fatigue interaction have been taken intoaccount using experimentally obtained material properties, as well as analytical and numerical calculations ofstress state, to estimate appropriate safety factors. Fatigue crack growth rate, da/dN, was also calculated,indicated that internal defects of circular or elliptical shape, found out by ultrasonic testing, do not affect reliableoperation of runner cover.
Keywords: Hydro power plant; Fatigue; Corrosion